1986
DOI: 10.1128/iai.53.3.711-712.1986
|View full text |Cite
|
Sign up to set email alerts
|

Effect of monophosphoryl lipid A on host resistance to bacterial infection

Abstract: The ability of monophosphoryl lipid A (MPLA) to enhance nonspecific host resistance to bacterial infections was studied. Mice were treated with MPLA prior to intraperitoneal challenge with Escherichia coli or Staphylococcus epidermidis. Animals received additional MPLA for 2 days postinfection, and survival rates were determined. Ten micrograms of MPLA per mouse significantly improved the survival of animals infected with either bacterial species. Dose-response studies showed significant MPLA-induced protectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 3 publications
0
23
0
Order By: Relevance
“…Among these bioactive derivatives is monophosphoryl lipid A (MPLA), produced by hydrolysis of the diphosphoryl lipid A found in wild‐type LPS 5 . MPLA has been found to protect mice against sepsis induced by Gram‐negative infection, caecal ligation and puncture and post‐haemorrhagic Staphylococcal infection 6 . The protective effect of MPLA in mice appears to be neutrophil dependent 7 .…”
mentioning
confidence: 99%
“…Among these bioactive derivatives is monophosphoryl lipid A (MPLA), produced by hydrolysis of the diphosphoryl lipid A found in wild‐type LPS 5 . MPLA has been found to protect mice against sepsis induced by Gram‐negative infection, caecal ligation and puncture and post‐haemorrhagic Staphylococcal infection 6 . The protective effect of MPLA in mice appears to be neutrophil dependent 7 .…”
mentioning
confidence: 99%
“…Results from phase I clinical trials demonstrated that the addition of MPL to recombinant herpes simplex virus type 2 and hepatitis B vaccines resulted in higher seroconversion rates and larger antibody (Ab) titers (reviewed in reference 62), illustrating the efficacy of MPL as an adjuvant. The ability of MPL to promote nonspecific resistance to infection and to induce a state of endotoxin tolerance analogous to that produced by LPS (2,10,33,42) has provided the rationale for the development of MPL as a prophylactic agent for septic shock. Pretreatment of experimental animals with MPL promotes improved survival rates following peritonitis, infection with either gram-negative or gram-positive bacteria, and shock induced by LPS, staphylococcal enterotoxin B, and tumor necrosis factor alpha (TNF-␣) (1,3,4,10).…”
mentioning
confidence: 99%
“…The ability of MPL to promote nonspecific resistance to infection and to induce a state of endotoxin tolerance analogous to that produced by LPS (2,10,33,42) has provided the rationale for the development of MPL as a prophylactic agent for septic shock. Pretreatment of experimental animals with MPL promotes improved survival rates following peritonitis, infection with either gram-negative or gram-positive bacteria, and shock induced by LPS, staphylococcal enterotoxin B, and tumor necrosis factor alpha (TNF-␣) (1,3,4,10). These protective effects have been largely attributed to the ability of MPL to induce a state of tolerance to subsequent endotoxin challenge that results in an attenuated systemic response to LPS (chills, fever, and tachycardia), ameliorated production of proinflammatory cytokines (TNF-␣, interleukin-6 , and IL-8), and inhibited development of disseminated intravascular coagulation (2-4, 30, 33, 66).…”
mentioning
confidence: 99%
“…Monophosphoryl lipid A (MPL or MPLA) is an effective and exceedingly safe and non-toxic adjuvant vaccine adjuvant (98)(99)(100)(101)(102)(103)(104)(105)(106)(107). It is a highly specific TLR4 agonist.…”
Section: Vaccine Adjuvant: Monophosphoryl Lipid Amentioning
confidence: 99%